Penegakan Hukum Dan Putusan Peradilan Kasus-Kasus Illegal Logging - Teguh Soedarsono (Fakultas Hukum Universitas Islam Indonesia, 2010)
This study reveals that verdict of illegal logging cases tried at district courts and supreme courts arises not only contradiction within legal officers but it also leads to arise a public controvercy. This occurs not only due to the inconsistency of understanding of pubic prosecutors and judges toward normative framework of illegal logging issue and anti corruption bill, but also because of the weakneses of moral integrity of legal officer who have a good relationship with actors of illegal logging. Establishing a steady of legal enforcement is necessary to be done in relation to illegal logging cases. A complexety of problem in illegal logging cases have been influeced by certain factors, lack of awarness of local community, public prosecutors and jusges generally use legal administrative approach is more dominant than integrated criminal legal system then the practice of legal enforcement towards illegal logging has failed to control effectively.Key word : Illegal logging, legal enforcement, corruption, and justice